Kinerja, produktivitas, dan integritas guru di Jawa Timur setelah lulus program pendidikan guru. - Rarasaning Satianingsih; Sunu Catur Budiyono; Kristiani; Akhmad Qomaru Zaman (PPPM STKIP PGRI Lamongan, 2023)
Professional teachers are certified teachers. One of the implementing institutions for teacher certification or PPG is the PGRI Adi Buana University in Surabaya, with one of its study programs being the PGSD study program. In accordance with one of the visions of PPG UNIPA Surabaya is to organize PPG which refers to the achievement of pedagogic, professional, personality and social competencies as well as being able to develop information technology-based learning and provide education for teaching staff so that PPG graduates of PGSD Study Program who have received educator certificates are expected to be able to become good teacher. professional. Teacher professionalism can be related to teacher performance and teacher motivation. The purpose of this study was to analyze the performance and motivation of teachers in East Java who graduated from the PGSD PPG Study Program. This type of research is quantitative research with descriptive methods. Sampling was carried out using probability sampling technique, which provides equal opportunities for all elements in the population. Data collection techniques using survey methods through questionnaires and interviews. Research instruments in the form of questionnaires and interview guidelines. Based on the measurement results through several aspects of PPG UNIPA Surabaya graduates are very good, this can be proven through the results obtained through measurement instruments which involve several aspects, starting from; a) the integrity aspect of the alumni is very good, b) compiling innovative learning shows that the competence of graduates in compiling and developing innovative learning is good,